Improving guest and owner satisfaction through a circular economy: An agritourism case study - Carvalho, P. T. de.; Raimundo, R. J.; Lopes, J. D. (Tourism and Hospitality, 2024)
This study examines the role of agritourism in developing strategies to promote a circular economy by applying the 3Rs (reduce, reuse, and recycle) and improving guests’ satisfaction. It contributes to filling the gap in the literature regarding the challenges posed, impact evidence, potential trade-offs, and socioeconomic considerations for the application of the 3Rs strategy in small tourism businesses. Interviews with hotel owners/hosts and guests were conducted through mainly qualitative methods, and the content was analyzed. This study reports on a case study conducted with a convenience sample of customers from a rural tourism company in Portugal to assess their position concerning the company’s 3Rs strategy. The case study reveals that common categories—hosts, breakfast, decoration, environment, and comfort—appreciated by guests align with the 3Rs practices. It was found that being environmentally responsible, taking part in the circular economy, and interacting with it can improve not only the satisfaction of guests but also hosts, thus creating memorable experiences for both. This study also shows that the position of customers regarding the 3Rs is not monolithic, with reusing and recycling emerging most prominently. This study shows that, in this context, a circular economy is feasible, provides tangible benefits, and successfully combines operational efficiency and guest convenience. This study also shows that it is possible to establish a successful tourism supply strategy based on a circular economy, particularly the 3Rs. Still, this strategy should not look at the 3Rs as if they were a uniform reality.